Troska o świat i zadanie jego wspólnej przebudowy, czyli o Korczakowskiej uwspólniającej utopii w działaniu - Karolina Starego (Problemy Wczesnej Edukacji)
The aim of this paper is to reconstruct Korczak’s notion of “utopia in action”. The notion is based on the philosophy of education concerned with creating of what is common. In this analysis I leave aside Korczak’s “paidocentrism” and focus on the communal elements in his thought – such as the care for the world that is also a call for its shared reconstruction, and the ontological force of love for the world and the people that populate it. Such an interpretation of Korczak’s thought allows it to become a topical alternative for the essentialist, antagonistic and exclusive ideas concerning community education.